The Effect of Topical 100% Sunflower Seed Oil (SSO) Extract on Trans Epidermal Water Loss (Tewl) and Skin PH Levels in a History of Atopic Dermatitis - Megawati, Yunitasari; Widayati, Retno Indar; Malik, Diah Adriani (Syntax Corporation Indonesia, 2024)
The skin barrier function can be disturbed in various conditions, one of which is atopic dermatitis (AD). Efforts to improve the skin barrier can be done by using various types of moisturizers. Natural oil from sunflower seed oil (SSO) can be used as